An empirical study on security expert ecosystem in the future IoT service environment. (May 2016) - Park, Sangho; Kim, Yanghoon; Chang, Hangbae
Abstract: As society become increasingly information-oriented, the use of cyberspace is also expanding, and people are exposed to various cyber-terror threats and security incidents. Additionally, according to the development of convergence security that extends from information security to all industrial sectors, the demand for an information security workforce has increased along with the development of the information security industry. Despite the expectation of a shortage of information security workforce due to the great demand surpassing the supply of available workers, the turnover among existing information security experts is very serious. The reasons why this turnover is such problem are as follows. First, the expert training system for the information security workforce is incomplete. Second, these experts do not receive an appropriate education for turnover in information security area or information as an insufficient data against the distribution or job mobility of the information security area though there are various occupations in information security area. Therefore, this paper will conduct research on the distribution of information security roles and the frequency of such job mobility in order to resolve these problems.